Authigenic ferrimagnetic iron sulfide preservation due to non‐steady state diagenesis: A perspective from Perseverance Drift, Northwestern Weddell Sea (Dataset) ... - Reilly, Brendan T.; McCormick, Michael L.; Brachfeld, Stefanie A.; Haley, Brian A. (Magnetics Information Consortium (MagIC), 2020)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Authigenic ferrimagnetic iron sulfide preservation due to non‐steady state diagenesis: A perspective from Perseverance Drift, Northwestern Weddell Sea ...